Computational Simulation of COX-1 (PDB: 3KK6) and COX-2 (PDB: 3LN1) Enzyme: 3D-QSAR Study, Docking Molecular and Simulation Dynamic on Series of Benzimidazole Derivatives - Bhor, Rohit Jaysing; Wani, Saiprasad Vasant; Thorat, Kaushal Arjun; Sadaphal, Omkar Balasaheb; Varpe, Tanmay Rajendra; Ghogare, Prajwal Vijendra; Bhosle, Shainesh Ganpat; Gadekar, Sanket Sunilrao (Asian Journal of Biological and Life Sciences, 2025)
Background: The proposed approach summarizes each activity in silico research. The structure-activity correlations and pharmacological effects of compounds containing benzimidazole are examined in this study. Using a variety of computational techniques, in silico studies allow for forecasting structural changes and how they would impact the pharmacological properties as well as the efficiency of these modifications. The computational study of benzimidazole derivatives is the main topic of this article. All compounds' cytotoxicity against inflammation was assessed, and the outcomes showed that several of them had strong inhibitions. Materials and Methods: The aim of this study was to investigate Cyclooxygenase-1 (COX-1) (PDB: 3KK6) and Cyclooxygenase-2 (COX-2) (PDB: 3LN1) enzyme inhibitory, and inflammatory activities of a new series of 1H-benzimidazole derivatives, for their possible use as multi-action therapeutic agents. Molecular Design Suite was used to conduct Combi Lab investigations and 3D-QSAR. Schrodinger Maestro was used for the molecular docking investigation. Results: Five compounds SW6; SW5; SW11; SW13 and SW15 in a library of 16 compounds created using a combinatorial approach demonstrated superior projected biological activity than the dataset's most active molecule. These chemicals exhibited proximal contact with amino acid residues on COX-2 (PDB: 3LN1) such as Phe381, Leu-384, Tyr-385, Trp-387, Phe-518, Gly-526, Met-522, Tyr348, Val-349, Leu-352. Conclusion: This study determined the structural elements affecting by carefully changing the substituents, ring modifications, and linker groups. The logical creation and optimization of more powerful and selective molecules is made possible by these discoveries. In contrast to the reference ligand, the current study produced more powerful benzimidazoles as inhibiting compounds for COX-1 (PDB: 3KK6) and COX-2 (PDB: 3LN1) with excellent interaction. The study's findings could aid in the creation of new COX-1 (PDB: 3KK6) and COX-2 (PDB: 3LN1) inhibitors to treat inflammatory conditions.
Keywords: ADMET; Benzimidazole; COX-1 (PDB: 3KK6); COX-2 (PDB: 3LN1); Inflammation; Molecular docking